Pre-steady state kinetics of DNA binding and abasic site hydrolysis by tyrosyl-DNA phosphodiesterase 1. Issue 11 (18th August 2017) - Kuznetsov, Nikita A.; Lebedeva, Natalia A.; Kuznetsova, Alexandra A.; Rechkunova, Nadejda I.; Dyrkheeva, Nadezhda S.; Kupryushkin, Maxim S.; Stetsenko, Dmitry A.; Pyshnyi, Dmitrii V.; Fedorova, Olga S.; Lavrik, Olga I.
Abstract : Tyrosyl-DNA phosphodiesterase 1 (Tdp1) processes DNA 3′-end-blocking modifications, possesses DNA and RNA 3′-nucleosidase activity and is also able to hydrolyze an internal apurinic/apyrimidinic (AP) site and its synthetic analogs. The mechanism of Tdp1 interaction with DNA was analyzed using pre-steady state stopped-flow kinetics with tryptophan, 2-aminopurine and Förster resonance energy transfer fluorescence detection. Phosphorothioate or tetramethyl phosphoryl guanidine groups at the 3′-end of DNA have been used to prevent 3′-nucleosidase digestion by Tdp1. DNA binding and catalytic properties of Tdp1 and its mutants H493R (Tdp1 mutant SCAN1) and H263A have been compared. The data indicate that the initial step of Tdp1 interaction with DNA includes binding of Tdp1 to the DNA ends followed by the 3′-nucleosidase reaction. In the case of DNA containing AP site, three steps of fluorescence variation were detected that characterize (i) initial binding the enzyme to the termini of DNA, (ii) the conformational transitions of Tdp1 and (iii) search for and recognition of the AP-site in DNA, which leads to the formation of the catalytically active complex and to the AP-site cleavage reaction. Analysis of Tdp1 interaction with single- and double-stranded DNA substrates shows that the rates of the 3′-nucleosidase and AP-site cleavage reactions have similar values in the case of single-stranded DNA, whereas in double-stranded DNA, the cleavage of the AP-site proceeds two times faster than 3′-nucleosidase digestion. Therefore, the data show that the AP-site cleavage reaction is an essential function of Tdp1 which may comprise an independent of AP endonuclease 1 AP-site repair pathway.